2018
DOI: 10.29267/mxjb.2018.3.4.70
|View full text |Cite
|
Sign up to set email alerts
|

Los microorganismos como una alternativa para la remediación de contaminación por hidrocarburos

Abstract: La contaminación es uno de los problemas más grandes a los que se enfrenta la humanidad actualmente; algunos compuestos pueden almacenarse por largos períodos en el suelo y mantos acuíferos. Además, los efectos nocivos sobre la salud humana son bien conocidos; el medio ambiente tiene la capacidad de restaurar las áreas contaminadas en bajas concentraciones; sin embargo, se han superado los límites naturales de degradación. Por ello, es importante la implementación de tecnologías de remediación para tratar suel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…T3 and T4 showed greater bacterial population at 89 days, but not in fungi whose greater populations showed at 79 days. Hydrocarbon degrading microorganisms have different capacities in the contaminated ecosystems to reduce the potential of the dangerous chemicals released in the environment (Domínguez-Sánchez et al, 2018). In general, the bacterial and fungal HC populations in soil increase significantly in time.…”
Section: Resultsmentioning
confidence: 99%
“…T3 and T4 showed greater bacterial population at 89 days, but not in fungi whose greater populations showed at 79 days. Hydrocarbon degrading microorganisms have different capacities in the contaminated ecosystems to reduce the potential of the dangerous chemicals released in the environment (Domínguez-Sánchez et al, 2018). In general, the bacterial and fungal HC populations in soil increase significantly in time.…”
Section: Resultsmentioning
confidence: 99%
“…There is also information regarding the synthesis of protein of unicellular origin as food for humans and animals 22,23 . Examples in nature include the genera Candida 24,25 , Cryptococcus, Pichia and Yarrowia [26][27][28] , as well as: Meyerozyma, Rhodotorula, Wickerhamia and Rhodosporidium 6 . Therefore, there is evidence that the yeast genus Saccharomyces has the potential to be exploited for the synthesis of protein of unicellular origin to produce low-cost food of excellent nutritional quality 22 as well as for the recovery of environments impacted by hydrocarbon mixtures, such as kerosene, by means of bioaugmentation, a process in which Saccharomyces would be fundamental for it to succeed 27. In this sense, it has been reported that Saccharomyces species have the biochemical capacity to utilize 12-to 16-carbon hydrocarbon fractions analogous to kerosene to mineralize them to CO2 and water 28 .…”
Section: Introductionmentioning
confidence: 99%